Representasi Generasi Z dalam Tren Wetonan di Media Sosial Tiktok - Baihaqi, Muhammad Maulana; Sukmawan, Sony (Universitas Negeri Padang, 2025)
This research aims to describe how Generation Z represents the tradition of pitungan weton through their interactions in the comment sections of TikTok, as well as to analyze how technological mechanisms—such as algorithms, visual content, and viral logic—shape their cognition and attitudes toward the tradition. The research adopts a qualitative paradigm grounded in Stuart Hall’s theory of representation (encoding–decoding model), while Dery’s concept of technoculture is used to understand how cultural meanings are interpreted, negotiated, or rejected within digital spaces. The findings reveal three decoding patterns: (i) dominant position (full acceptance of cultural meaning), (ii) negotiated position (adjustment between cultural values and personal experience), and (iii) oppositional position (rejection of tradition). These representations are not merely individual expressions, but also reflect a broader collective discourse among Generation Z in responding to local culture through digital media.